(untitled) (Philological Studies, 2019)
This paper examines the mutual adaptability and conformity of characters and syuzhets of epic poetry, i.e. the level of their compatibility. Fluid models are open to a large number of epic names or various types of heroes, contrary to crystallized models with a hardened structure, demanding precisely determined types of protagonists or even precise epic names. Analogously, from the character’s perspective, we can differentiate between fluid and crystallized characters. The former ones can adapt to numerous syuzhet models, while the latter enter a very limited number of models, either because of the underdeveloped epic biographies, or because of their dominant typical trait that limits their progress through syuzhets. The majority of models and characters occupy the middle ground between complete crystallization and high fluidity – partially fluid (or partially crystallized) syuzhets i.e. characters.